Транскордонний бренд: постановка питання - Тихомирова, Євгенія Борисівна; Tykhomyrova, Yevheniia B. (Київський національний університет імені Тараса Шевченка, 2015)
The article presents a study of the concept "transboundary brand" and the analysis of the formation of cross-border branding practices in transboundary areas of Europe and Ukraine. Today, the cross-border territory, united by common economic, social, cultural and political life, strive to be transformed into a brand. That is why the issues related to their positioning and branding. According to the author, cross-border / inter-regional brand - an intangible asset of cross-border cooperation, which provides the promotion of the interests of cross-border areas, both inside and outside your cross-border. In recent years such brands as part єvroregionov formed with the participation of many European countries.
Keywords: стратегія брендингу; транскордонний бренд; транскордонний кластер; Єврорегіон